Pengukuran Kinerja Karyawan Menggunakan Metode Balanced Scorecard Di PT. Nusantara Batulicin - Oscar, Agus Wiramsya (Brahmana : Jurnal Penerapan Kecerdasan Buatan, 2023)
Research has been carried out on how to apply the Balance Scorecard as a benchmark for employee performance at the Rubber Factory at PT. Nusantara Batulicin PT. Nusantara Batulicin is a private company located in South Kalimantan province in Tanah Bumbu district which operates in the rubber industry, bearing in mind that rubber in the Covid-19 and post-Covid-19 era experienced unpredictable price changes, initially the price of rubber reached Rp. 12,000,- per kilogram to Rp. 2,000,- per kilogram which of course has a big impact on the performance of the company's employees. Based on the results of the research that has been carried out, the conclusion obtained is that the results of research using the application of the Balanced Scorecard in this research based on the four perspectives are in the good category. The financial perspective regarding the company's sales or income is in the positive category or making a profit from its business results, although in 2019 it experienced a loss but can be improved in 2020 and 2021. The customer perspective in terms of market share is correct, apart from that the company also provides maximum service so that customers feel satisfied and customer retention can be maintained. The internal business perspective from an innovation perspective always provides different innovations so that it can improve the quality of production results. Apart from that, from the operational aspect, the operational process is in accordance with the standards and procedures set by the government.